Analisis Ergonomi Posisi Duduk dan Desain Kursi terhadap Keluhan Nyeri Punggung Bawah pada Mahasiswa Kedokteran Universitas Tarumanagara - Tia Aura Caroline; Octavia Dwi Wahyuni (Pusat Riset dan Inovasi Nasional, 2026)
Low back pain is a musculoskeletal disorder characterized by pain in the lumbar region. The occurrence of low back pain is often associated with improper ergonomics, particularly related to sitting posture and the design of seating used. These conditions may lead to increased static load on the lumbar spine, resulting in excessive stretching of muscles and ligaments, impaired muscle circulation, and decreased strength of the back and abdominal muscles. Over time, these biomechanical changes can contribute to the development of low back pain. The aim of this study was to analyze the relationship between sitting posture ergonomics and chair design with complaints of low back pain among medical students at Tarumanagara University. This study was an observational analytic study with a cross-sectional design conducted from March to August 2025 involving 232 subjects from the Faculty of Medicine, Tarumanagara University, selected using simple random sampling. Data were collected through self-administered questionnaires using Google Forms, anthropometric measurements using a measuring tape, and photographic documentation of sitting posture taken by the researchers. This study obtained ethical clearance and research permission. Data were analyzed using SPSS with the Chi-square test. The results showed a significant association between sitting posture and complaints of low back pain (p-value = 0.042; PRR = 1.68), as well as between chair design and low back pain complaints (p-value = 0.046; PRR = 2.52).In conclusion, there is a significant relationship between sitting posture ergonomics and chair design with complaints of low back pain among medical students at Tarumanagara University.